Sustainable Pavement Engineering and Road Materials - Bocci, Edoardo (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
In a similar way to many other engineering fields, the road pavement industry strongly affects the critical issues of our generation, including climate change, pollutant emission, the exploitation of natural resources and economic crises. For this reason, technicians and researchers are searching ravenously for sustainable solutions to implement in current road construction systems with the following goals: To reduce the consumption of energy and virgin materials; To run environmentally and economically friendly maintenance; To recycle waste from different industrial processes; To decrease the noise, the pollution and the heat generated by traffic, particularly in urban contexts. This Special Issue aims to collect high-quality studies that combine the aforementioned solutions, including works pertaining to: The hot, warm, and cold recycling of reclaimed asphalt pavement; Marginal materials for asphalt pavements; Innovative sustainable materials; Durability and environmental aspects; Structure performance, modeling and design; Advanced trends in rehabilitation and preservation; Surface characteristics and road safety; Management system/life cycle analysis; Urban heat island mitigation; Energy harvesting.